Pulmonary Coccidioidomycosis - Kimes, Kathryn E.; Kasule, Sabirah N.; Blair, Janis E. (Seminars in Respiratory and Critical Care Medicine, 2020)
Coccidioidomycosis is an infection caused by the geographically restricted dimorphic fungus, Coccidioides. Coccidioidomycosis occurs endemically in the southwestern and western United States, mainly in focused regions of Arizona and California where the incidence is highest, and in Central and South America. Patients with impaired immunity, especially those with impaired cellular immunity, are at higher risk of severe and disseminated disease. In this review, we describe the fungal ecology and mycology, epidemiology, pathophysiology, and normal immune defenses to Coccidioides as well as address current concepts in diagnosis, treatment, and continued care of patients with pulmonary coccidioidomycosis. We also present and answer our most frequently asked questions regarding patients with primary pulmonary coccidioidomycosis.
Keywords: Coccidioides; coccidioidomycosis; pneumonia; valley fever